2021
DOI: 10.3389/fcell.2021.700276
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mRNA Processing Factors and Retinitis Pigmentosa: RNA Splicing and Beyond

Abstract: Retinitis pigmentosa (RP) is the most common inherited retinal disease characterized by progressive degeneration of photoreceptors and/or retinal pigment epithelium that eventually results in blindness. Mutations in pre-mRNA processing factors (PRPF3, 4, 6, 8, 31, SNRNP200, and RP9) have been linked to 15–20% of autosomal dominant RP (adRP) cases. Current evidence indicates that PRPF mutations cause retinal specific global spliceosome dysregulation, leading to mis-splicing of numerous genes that are involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 231 publications
(302 reference statements)
0
19
0
Order By: Relevance
“…A severe decrease in photoreceptor cell layer has been reported in the zebrafish by using Prfp31 morphants 51 , and the presence of apoptotic nuclei was previously observed in photoreceptors within late retinal organoids derived from PRPF31 patients iPSCs 29 . However, no defective photoreceptor phenotype was reported in different mouse models of splicing factors-linked RP 23 , 24 , 47 . It is not known why Prpf31 mutant mice have only an RPE degenerative phenotype and do not present the key phenotype of PRPF31 -related RP patients, i.e .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A severe decrease in photoreceptor cell layer has been reported in the zebrafish by using Prfp31 morphants 51 , and the presence of apoptotic nuclei was previously observed in photoreceptors within late retinal organoids derived from PRPF31 patients iPSCs 29 . However, no defective photoreceptor phenotype was reported in different mouse models of splicing factors-linked RP 23 , 24 , 47 . It is not known why Prpf31 mutant mice have only an RPE degenerative phenotype and do not present the key phenotype of PRPF31 -related RP patients, i.e .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using human post-mortem retinas or patient lymphoblast cell lines showed the absence of specific PRPF31 isoforms in the retina, as well as both steady-state levels of snRNAs and processed pre-mRNAs highest in the retina, indicating the requirement of a particularly elevated splicing activity in this tissue 22 . Furthermore, the identification of which retinal cell type (RPE and/or photoreceptors) is primarily affected by mutations in the RNA splicing factors lead to a scientific debate 13 , 47 . To gain insights into PRPF31 -related RP, we characterized the cellular phenotype of RPE cells and retinal organoids derived from both clinically asymptomatic carriers and affected PRPF31 patients carrying two different mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 75 ] Variational hotspots for RP are associated with the U4 snRNP binding channel. [ 76 ] In a zebrafish model, it has been observed that variants affect this unwinding and result in rod cells demorphogenesis. But the pathogenic mechanism is yet unclear.…”
Section: Retinitis Pigmentosa1 Genementioning
confidence: 99%
“…In contrast to these mutations, mutations in EXOSC2 are linked to a distinct syndrome, characterized by short stature, hearing loss, retinitis pigmentosa, and distinctive facies (SHRF), where the cerebellar atrophy is mild [92]. Given that mutations in pre-mRNA processing factors (PRPF3, PRPF4, PRPF6, PRPF8, PRPF31, SNRNP200, and RP9) have been linked to 15-20% of autosomal dominant retinitis pigmentosa, retinitis pigmentosa of EXOSC2-associated SHRF may be associated with misprocessing of pre-mRNAs and snR-NAs [93]. As other examples, mutations in PABPN1 have been linked to oculopharyngeal muscular dystrophy (OPMD) [94].…”
Section: Mutations In Rna Exosome Components and Rare Diseasesmentioning
confidence: 99%